The Role of Financial Statement Analysis in the Assessment of Financial Performance of enterprises: Case Study of Maintenance Company for the East - CHORFI, Moncef; BOUCHELAGHEM, Amirouche (Journal of Human Sciences, 2020)
The objectives of this study were to identify the role of the Financial Statement Analysis in the assessment of financial performance of companies containing quantitative and qualitative information that represents accounting data for previous and current years, in addition to predict his future. A number of results, including the financially balanced of Maintenance Company for the East, despite the existence of certain deficiencies in carrying out its tasks and activities by neglecting the financial analysis, the fact that they do not surround themselves with commotions. Finally, it is recommended that the company capitalize on the opportunities that increase its profitability in the future and thus realize the greatest profit margin compared to what is currently achieved.